Peranan Budaya Hukum Kementerian Lingkungan Hidup dan Kehutanan Dalam Penetapan Hutan Adat - Daru Adianto; Muamar (Jurnal Suara Hukum, 2022)
After the decision of the Constitutional Court Number 35/PUU-X/2012 which stated that customary forests are not part of state forests but private forests provide legal certainty and protection of the rights of indigenous peoples in managing customary forests. As a follow-up to this decision, the Ministry of Environment and Forestry established Minister of Environment and Forestry Regulation P.32/Menlhk-Setjen/2015 concerning Private Forests which has been renewed through Minister of Environment and Forestry No.9 of 2021 concerning Management of Social Forestry. Until now, the number of customary forests that have been determined is 107 customary forest units. One of the factors supporting the increase in the number of customary forests is a change in the internal legal culture of the LHK when verifying and validating customary forest applications. Based on the results of the research, facts and problems were found, one of which was related to the requirements for recognition of legal subjects for groups holding rights through regional legal products which could be in the form of Regional Regulations (PERDA). The PERDA contains the Recognition and Protection of Indigenous Peoples and the areas managed by these communities. Some PERDAs are not included with maps of customary territories or there are no other regional legal products that define the boundaries of the community's managed areas. In addition to the problems of legal subjects and areas of management, changes in the legal culture within a government institution also have an influence on the process of recognizing these rights. This writing uses an empirical legal research approach by examining the roles of the legal culture of the Ministry of Environment and Forestry in determining customary forests